2022
DOI: 10.1021/acsanm.1c03959
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Hydrogels Assembled from Enzyme-Adsorbed Mesoporous Silica Nanostructures for Thermoresponsive Doxorubicin Release

Abstract: The development of nanocomposite supramolecular hydrogels, which can be activated by local or external stimuli (pH, redox, enzyme, heat), is highly promising for various applications including implantable materials for antitumor or tissue engineering applications. Here, we show that large pore stellate mesoporous silica modified with isobutyramide grafts allow >100% wt. loading of enzymes, which ensures through the enzyme-assisted self-assembly an easy, rapid, and efficient way to design smart thermoresponsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…As a biosensing material, hydrogels prepared by enzymatic methods have the advantages of high sensitivity, strong specificity, and low detection limits. , These hydrogels were the earliest commercialized biosensor, and they have been used for the detection and analysis of multiple components. The development of cross-linking enzymes provides sensors with new materials and methods, and it will likely bring major changes to the field of biosensors. As shown in Figure d, the hydrogel prepared by the enzymatic method was applied to the biosensors. Studies have reported that a new type of dienzyme (lagen peroxidase and glucose oxidase)/poly­(amino) sulfonate hydrogel sensor could determine lactic acid levels, and the sensor responded quickly (2 s) with a short recovery time (2 min). The total test time of this sensor was 4 min, which was faster than the commercial lactic acid detection, which typically requires up to 10 min …”
Section: Applications Of Enzyme-prepared Hydrogelsmentioning
confidence: 99%
“…As a biosensing material, hydrogels prepared by enzymatic methods have the advantages of high sensitivity, strong specificity, and low detection limits. , These hydrogels were the earliest commercialized biosensor, and they have been used for the detection and analysis of multiple components. The development of cross-linking enzymes provides sensors with new materials and methods, and it will likely bring major changes to the field of biosensors. As shown in Figure d, the hydrogel prepared by the enzymatic method was applied to the biosensors. Studies have reported that a new type of dienzyme (lagen peroxidase and glucose oxidase)/poly­(amino) sulfonate hydrogel sensor could determine lactic acid levels, and the sensor responded quickly (2 s) with a short recovery time (2 min). The total test time of this sensor was 4 min, which was faster than the commercial lactic acid detection, which typically requires up to 10 min …”
Section: Applications Of Enzyme-prepared Hydrogelsmentioning
confidence: 99%
“…Several parameters need to be taken into account in order to obtain the requisite therapeutic effect which is necessarily monitored throughout the course of different stages of design [52] . Furthermore, the hydrophilicity or hydrophobicity of drugs, the passage, and the biodegradability of drugs tend to alter the interactions amongst the drug components which serves as one of the several factors [53–56] . The challenge lies in systematic monitoring of the two: the rate at which the drug release occurs and the biodegradation; making sure both circulate systematically at full capacity.…”
Section: Drug Loading and Drug Releasementioning
confidence: 99%
“…Driven by noncovalent interactions, peptide self-assembly has received considerable attention for its wide biomedical applications including cancer and bacterial therapy, tissue engineering, immune modulation, , and drug delivery. In this work, we utilized a de novo designed self-assembling peptide to construct a bacterium trapping system with high strain selectivity. As shown in Figure , the designed molecule N-K10 contains a binding domain, a linker, and a self-assembling motif.…”
Section: Introductionmentioning
confidence: 99%